2013
DOI: 10.1111/1475-6773.12092
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Patient and Nurse Short Forms of the Readiness for Hospital Discharge Scale and Their Relationship to Return to the Hospital

Abstract: Objective. To validate patient and nurse short forms for discharge readiness assessment and their associations with 30-day readmissions and emergency department (ED) visits. Data Sources/Study Setting. A total of 254 adult medical-surgical patients and their discharging nurses from an Eastern US tertiary hospital between May and November, 2011. Study Design. Prospective longitudinal design, multinomial logistic regression analysis. Data Collection/Extraction Methods. Nurses and patients independently completed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
188
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 114 publications
(199 citation statements)
references
References 25 publications
9
188
0
2
Order By: Relevance
“…Nurses and patients independently completed the questionnaire on the day of discharge. Nurse judgement of low discharge readiness was associated with a six-to nine-fold increase in readmission risk; however, patient self-assessment was associated neither with readmission nor with visits in emergency department [19]. Patient self-assessment is a purely subjective assessment, while nurse evaluation is more objective [20,21].…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Nurses and patients independently completed the questionnaire on the day of discharge. Nurse judgement of low discharge readiness was associated with a six-to nine-fold increase in readmission risk; however, patient self-assessment was associated neither with readmission nor with visits in emergency department [19]. Patient self-assessment is a purely subjective assessment, while nurse evaluation is more objective [20,21].…”
Section: Discussionmentioning
confidence: 98%
“…Readmission rates, however, were similar between the groups [18]. Weiss et al [19] validated a short, eight-item version of RHDS for discharge readiness assessment, its associations with 30-day readmissions, and emergency department visit rates. Nurses and patients independently completed the questionnaire on the day of discharge.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7] What we learned from this research was that the quality of discharge teaching impacted readiness for discharge and, ultimately, post-discharge coping difficulty and readmission. Specifically, we found that how nurses teach impacts these outcomes; [6] in the presence of poor quality teaching, content delivered is not necessarily content well received.…”
Section: Introductionmentioning
confidence: 91%
“…In developing a measure of discharge teaching for these studies, we reviewed literature on discharge teaching and general patient teaching sources. [7][8][9][10][11][12] What emerged from this review were four evidence-based approaches to discharge teaching (patient engagement, adult learning theory, motivational interviewing, and the teachback method) and 13 teaching skills aligned with these approaches. Through triangulation methods, [12] a synthesized model, the Theoretical Framework to Guide Patient/Family Teaching emerged.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation